Experimental investigation of direct-formed square and rectangular hollow section beams. (November 2021) - Tayyebi, Kamran; Sun, Min; Karimi, Kian; Daxon, Ray; Rossi, Brandon
Abstract: This paper presents an experimental study on the flexural behaviours of new-generation direct-formed square and rectangular hollow sections (collectively referred to as RHS herein). A total of 22 beam specimens covering wide ranges of cross-sectional dimensions and nominal yield stresses (350 and 690 MPa) are tested. The results are compared to those from previously tested indirect-formed and hot-finished RHS to study the effect of different production processes. The effects of post-production hot-dip galvanizing on residual stresses and flexural behaviours are also studied. The applicability of slenderness limits and flexural design formulae in the current North American steel design standards are examined using the experimental data. The experimental results demonstrate that the existing flexural design rules are generally conservative for direct-formed RHS (ungalvanized and galvanized). Graphical abstract: Unlabelled Image Highlights: Testing of 22 full-scale RHS beam specimens (regular- and high-strength steels) Comparisons between direct-formed, indirect-formed and hot-finished RHS Slenderness limits in current design standards are conservative for direct-formed RHS Flexural design rules in current standards are conservative for direct-formed RHS The effects of post-cold-forming hot-dip galvanizing are studied